Levels of some micronutrient in dried and fresh fruit samples of apricot cultivars - Davarynejad, D. G.; Hamed, K.; Nyéki, J.; Szabó, Z.; Nagy, P. T. (International Journal of Horticultural Science, 2012)
Concentration of Boron (B), Copper (Cu), Iron (Fe), Magnesium (Mg), Manganese (Mn) and Zinc (Zn) was analyzed in fresh and dried fruit samples of “Jumbo cot“, “Tom cot“, “Gold strike“, “Gold bar“, “Bergeron“, “Bergrouge“, “Sweet cot“, “Yellow cot“ and “Zebra“ apricot cultivars. Concentration of the studied elements was strongly affected by cultivars. B, Cu, Fe, Mn and Zn content of “Tom cot“ was significantly higher than other cultivars. “Gold strike“ had the highest amount of Mg. Similar tendency was observed in “Zebra“ and “Sweet cot“ where Mn content was significantly higher than the other element contents.